If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(-5-6w)=4(w+3)
We move all terms to the left:
-(-5-6w)-(4(w+3))=0
We add all the numbers together, and all the variables
-(-6w-5)-(4(w+3))=0
We get rid of parentheses
6w-(4(w+3))+5=0
We calculate terms in parentheses: -(4(w+3)), so:We get rid of parentheses
4(w+3)
We multiply parentheses
4w+12
Back to the equation:
-(4w+12)
6w-4w-12+5=0
We add all the numbers together, and all the variables
2w-7=0
We move all terms containing w to the left, all other terms to the right
2w=7
w=7/2
w=3+1/2
| -28=-8u+4(u-2) | | -2|3x+7|=9 | | 5x-2(2-1)=6 | | -8=-15/6(2)+b | | 18w+5=20w-17 | | 3(x-0)+9=-20 | | 85=-6y+7+4y | | -7x+1=5-7x | | 2w+20=120 | | 3x-10=x+40* | | 2x+11.5=22.5 | | 4x+4-x=19 | | -8(-7-6p)=12+4p | | x+5+8=15 | | –5j−–14j−–17=–10 | | (m-3)/4=-9 | | -4r-32=-67 | | -2=9/7p | | 4.3+10m=6.48 | | 94/63=x/82 | | 17r+12=16r | | 2x-4=(2x-1)2 | | 9+2m/3=12-m | | -144(3.14)=-12(3.14k) | | 3/4(28x+32)-6=-1/3(24x-24) | | {3x-2}{5}={7}{10} | | 3x-9=65 | | 3(4x-2)=-2(3+6x) | | 18/4=x/6 | | 5+2x+12=x+17 | | 6y+16=14y | | 4(p+8)=-2(p–4) |